HAMBATAN IMPLEMENTASI PERATURAN PEMERINTAH NO. 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH DI SAMARINDA - Dewy Handiny (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT Land registration is an important thing for every landowner to do. In the beginning, the lands belonged to the community did not have any documents at all. To indicate and determine that a person is a landowner, it is marked with certain objects as boundaries, such as pacak, stone, wood or tree.Land is one of the most important natural resources and takes a lot in human life. Man and land are two things that have strong attachments. The land gives a lot to humans and humans really interpret the importance of the land.Through Article 5 and Article 6 of Government Regulation No.24 of 1997 it is affirmed that the implementation of land registration is the National Land Agency and the implementation of land registration is conducted by the Head of Land Office in every Regency and City.